Ecotourism, social and human capitals, and identity valorization: the communities of Tapajós (PA), Brazil - Lima, Ismar Borges de; d'Hauteserre, Anne-Marie (Revista Brasileira de Ecoturismo (RBEcotur), 2011)
This article deals with the role of community-based ecotourism for strengthening human and social capitals as well as for enhancing culture and forest livelihood of riverbank dwellers in the Tapajós region, in central Amazonia. The research was done based on the premise that ecotourism can be a potential avenue for putting in evidence local culture, identity and singular lifestyles as while it can contribute to strengthen the local networks which can result in collective material and immaterial advantages. The analysis examines the hypothesis that outsiders (the tourists) once they travel to and stay with local communities, they become the primary agents who are in a position to perceive the main aspects of values, beliefs and routines as particularities of an Amazonian livelihood. Even though the visitors usually stay a few days in a certain community, they end up paying enough attention to what the locals tell and do. This way, the tourists involuntarily put the locals at the centre of their visit, to the extent the locals start realizing how important their forest lifestyle is. This argument certainly does not aim at validating the “spetacularisation” of forest people, of their environment and of their culture. Instead, the authors are rather interested in the processes through which outsiders can direct or indirectly – as ecotourism participants - contribute to improve the quality of life and to raise self-esteem of riverbank dwellers. Some Amazonian peoples (of remote areas) usually have a feeling of periphery and of marginalization, because they do not take part in the ‘developed metropolitan world’. The self-esteem factor gets relevance in an academic debate, because the Amazonian peoples hold a feeling of being periphery and marginal in reason of not being part of a ‘developed metropolitan world’; and this may cause adverse effects on their attitude and expectations. The investigation has a qualitative approach in order to produce descriptive data. Open and semi-structured interviews and participant observation were the main methods used for getting information from the riverbank dwellers.